A guide for proper utilisation of stable isotope reference materials*. Issue 2 (4th March 2019) - Meier-Augenstein, Wolfram; Schimmelmann, Arndt
ABSTRACT: Many scientific publications about stable isotope ratios suffer from flawed practices regarding calibration and normalisation of raw δ values in conjunction with prescribed δ values of reference materials. Violations of the identical treatment principle with regards to samples and standards (i.e. reference materials) and lack of adherence to SI-mandated and IUPAC-recommended nomenclature exacerbate the widespread problem of lackadaisical analytical practice and reporting. Science is supposed to strive for exactness, whereas ambiguity and jargon confound interdisciplinary communication. This contribution aims to expose typical misconceptions and avoidable errors and offers guidance toward the reproducible generation of isotope data, isotopic scale normalisation, and proper data reporting. We offer a comprehensive overview of sources of light stable isotope reference materials to best match sample matrices encountered by stable isotope practitioners with chemically similar reference materials.